Keikutsertaan Wanita dalam Politik Praktis Perspektif Hukum Islam - Sri Ujiana Putri; Asnawati Patuti; Zulfiah Sam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to find out a general overview of women's participation in political parties and how Islam views the role of women in the realm of practical politics. This research uses qualitative research, which focuses more on aspects of in-depth understanding, and uses library research methods with a normative juridical legal approach. The research results found that: (1) Based on Law number 2 of 2011 Article 2 paragraph 2, 30% representation of women can produce decisions that pay more attention to the interests and experiences of women who have been underrepresented; (2) There are differences of opinion regarding the law on women's participation in practical politics. The strongest opinion was the opinion of the majority of ulama who decided that women were not allowed to participate in practical politics. This is based on the strength of the arguments, in addition to the fact that there are no other arguments that contradict these arguments, as well as targeted criticism of the arguments that both allow and cancel their arguments with these arguments.